Pelatihan Manajemen Pemasaran Berbasis Transaksi Elektronik melalui Pemanfaatan Market Place untuk Peningkatan Kesejahteraan Masyarakat Komplek Perumahan Graha Mentarau - Husna, Lenny; Realize, Realize; Putri, Anggia Dasa (ASOSIASI IDEBAHASA KEPRI, 2024)
This community service aims to introduce and increase the public's understanding of the Graha Mentarau housing complex regarding electronic transaction-based marketing management through the use of the marketplace. In this context, the application of the Information and Electronic Transactions Law (UU ITE) becomes relevant because it regulates legal aspects related to electronic transactions, including consumer protection, data security and online business regulations. This training not only aims to improve practical skills in selling online but also to ensure that these activities comply with applicable legal provisions. Through interactive workshops and direct mentoring, training participants will be equipped with knowledge on how to effectively manage their online business, while understanding the legal responsibilities that must be complied with. It is hoped that the results of this training can make a significant contribution in increasing people's income and economic welfare, as well as strengthening compliance with the ITE Law in the context of marketplace utilization in the current digital era.